Red cell alloimmunization among antenatal women attending tertiary care center in Jamnagar, Gujarat, India - Dholakiya, Spruha Kashyap (Asian J Transfus Sci, 2021)
BACKGROUND: The following study was conducted to measure the presence of alloantibodies of Rh and other blood group antigens produced due to fetomaternal hemorrhage in all antenatal women as well as those leading to hemolytic disease of fetus and newborn; presenting to a tertiary care center, G.G. Government Hospital, Jamnagar, Gujarat, India, between April 2014 and March 2016 (2 years). MATERIALS AND METHODS: All multiparous women irrespective of their period of gestation or obstetrics history were included whereas those having taken anti-D immunoprophylaxis or with a history of blood transfusion were excluded. Antibody screening and identification were done using Bio-Rad ID microtyping system. RESULTS: Out of total 8920 multigravida females, 8488 were D-antigen positive whereas 432 were D-antigen negative. A total of 126 antibodies among 117 females (1.31%) were found; out of them, 33 were found in D-antigen positive females (0.39%) and 84 in D-antigen negative ones (19.44%) looking at overall frequency of other antibodies such as anti-C: 9, anti-c: 9, anti-E: 13, anti-Cw: 1, anti-M: 5, anti-S: 8, anti-Fya: 3, and anti-D: 78; it was found that anti-D is the most common. CONCLUSION: The rate of alloimmunization in D-antigen negative women was found to be very high as compared to other studies in western region; hence, strict follow-up of immunoprophylaxis of all Rh D-negative women needs to be taken care of. Apart from this, D-antigen-positive women also show alloimmunization against various antigens giving the prevalence of 0.39%; hence, it should be mandatory that there should be one standard universal protocol for screening of all antenatal women.